Konsep dan Implementasi Perbankan Syariah dan Manajemen Pendidikan Islam di Era Industri 4.0 - Rustya, Dian; Fuad, Moch Syifa'ul (Jurnal Perbankan Syariah, 2025)
The Industrial Revolution 4.0 is a form of industrial transformation characterised by the emergence of digital and physical technology integration, which has begun to change the way of production, distribution, and consumption. The use of technology in various aspects of life, including education and the economy, encourages product innovation to keep pace with the times. The issues in this study are 1) how the theoretical concepts of Islamic Banking and Islamic Education Management should be reconstructed/adapted in the era of Industry 4.0, 2) how Islamic Banking and Islamic Education Management (MPI) are implemented in educational institutions in facing the challenges of the Industry 4.0 era, and 3) how a synergy strategy can be built between Islamic Banking and MPI institutions in producing competent human resources in the 4.0 era. This research applies a descriptive qualitative method with a focus on literature research. The concept of ideal Islamic banking and Islamic education governance in the Industry 4.0 era needs to be harmonised. The Islamic banking sector acts as a provider of funds for education financing using qardh or ijarah, while ideal Islamic education acts as a producer of Sharia 5.0 Human Resources. The implementation of Islamic banking and Islamic education management has its own challenges. These challenges include the emergence of a digital divide in society, ever-changing government regulations, and the application of Islamic values in accordance with the conditions and demands of the Industrial Revolution 4.0 era. The development of the 4.0 Industrial Revolution era requires synergy between Sharia Banking and Islamic Education Management, where Sharia Banking provides capital for infrastructure development and Islamic Education provides the human resources to implement the existing system in society.